Performance measurement for not-for-profit organizations : the performing arts. - Han, Madeline Huixian. (2008)
The effectiveness of arts groups must be addressed before Singapore can become a Renaissance City for the Arts. Using the Balanced Scorecard, performance indicators were developed for the arts organizations. Findings from interviews and surveys showed that it is feasible to implement the BSC framework through the Performing Arts Scorecard.